2015
DOI: 10.1007/s13277-015-3346-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncocers: ceRNA-mediated cross-talk by sponging miRNAs in oncogenic pathways

Abstract: Competing endogenous RNAs (ceRNAs) are RNA transcripts which can communicate with each other by decreasing targeting concentration of micro-RNA (miRNA) with the derepression of other messenger RNAs (mRNAs) having the common miRNA response elements (MREs). Oncocers are ceRNAs taking crucial roles in oncogenic pathways processed in many types of cancer, and this study analyzes oncocer-mediated cross-talk by sponging microRNAs (miRNAs) in these pathways. While doing this, breast, liver, colon, prostate, gastric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
128
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 53 publications
2
128
0
Order By: Relevance
“…Any disturbance of this system may trigger a series of pathological processes in different human diseases, including cancers [29]. XIST inhibited cell proliferation and mobility in osteosarcoma by interacting with miR-21-5p and upregulating programmed cell death 4 (PDCD4) expression [30].…”
Section: Discussionmentioning
confidence: 99%
“…Any disturbance of this system may trigger a series of pathological processes in different human diseases, including cancers [29]. XIST inhibited cell proliferation and mobility in osteosarcoma by interacting with miR-21-5p and upregulating programmed cell death 4 (PDCD4) expression [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, lncRNAs may function as competing endogenous RNAs (ceRNAs), namely, miRNA sponges or antagomirs, to downregulate the expression and activities of miRNAs, thereby modulating the derepression of miRNA targets and imposing an additional level of posttranscriptional regulation. The ceRNA-miRNA-mRNA regulatory interactions maintain the overall activity and functional balance of gene networks in a cell, and any perturbation of this system may lead to pathological processes such as cancer [8]. Thus, the complex mechanism underlying ceRNAs in cells is a fresh perspective for researchers to explore the language of RNA molecules and gene expression networks in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies suggested that lncRNAs could function as a competing endogenous RNA and sponge miRNAs, thus regulating the expression of target mRNA [11]. For example, Jiao et al showed that lncRNA UCA1 enhanced cell proliferation through functioning as a ceRNA of Sox4 in esophageal cancer [12].…”
Section: Introductionmentioning
confidence: 99%